Single master regulatory gene coordinates the evolution and development of butterfly color and iridescence - Zhang, Linlin (Proc Natl Acad Sci U S A, 2017)
The optix gene has been implicated in butterfly wing pattern adaptation by genetic association, mapping, and expression studies. The actual developmental function of this gene has remained unclear, however. Here we used CRISPR/Cas9 genome editing to show that optix plays a fundamental role in nymphalid butterfly wing pattern development, where it is required for determination of all chromatic coloration. optix knockouts in four species show complete replacement of color pigments with melanins, with corresponding changes in pigment-related gene expression, resulting in black and gray butterflies. We also show that optix simultaneously acts as a switch gene for blue structural iridescence in some butterflies, demonstrating simple regulatory coordination of structural and pigmentary coloration. Remarkably, these optix knockouts phenocopy the recurring “black and blue” wing pattern archetype that has arisen on many independent occasions in butterflies. Here we demonstrate a simple genetic basis for structural coloration, and show that optix plays a deeply conserved role in butterfly wing pattern development.